(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article analyzes breast cancer, its early diagnosis pathways and modern treatment methods. During the study, the relevance of the disease, the main risk factors, and approaches to diagnosis were considered. Scientific sources and statistical data analysis became the basis as the methodology. As a result of the study, it was proved that early diagnosis and comprehensive treatment is the main factor in reducing the consequences of the disease. The importance of prevention and routine screening was emphasized as the main conclusion.